(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify the effect of using the method of questioning on the immediate and delayed achievement of the subject of methods of teaching physical education.The researcher used the experimental method, and the research sample consisted of third-stage students - Department of Physical Education - College of Basic Education - Al-Mustansiriya University, where the research sample consisted of (32) male and female students, who were selected in a simple random way, and they were divided into two groups, one of which was experimental, studied according to the method of questioning The other is a female officer who studied according to the method used. The research tools were determined by the immediate and deferred achievement test in the subject of methods of teaching physical education, and the validity and reliability of the two tools were confirmed.